Sodno preizkušanje primernosti menjalnega razmerja ali denarne odpravnine manjšinskim delničarjem - Prelič, Saša (Podjetje in delo, 2018)
The article discusses the peculiarities of a judicial test of an exchange ratio and adequacy of appraisal remedy. The author examines the legal positions that entitle shareholders to obtain shares according to the appropriate exchange ratio or to obtain appraisal remedy. Adequacy of the aforementioned rights is legally admissible only within special judicial procedure.
Keywords: deleži; denarna odpravnina; menjalno razmerje; poravnalni odbor; sodni preizkus